Efficacy of an Emergency Department-based Motivational Teenage Smoking Intervention - Kimberly Horn, EdD; Geri Dino, PhD; Candice Hamilton, MPH; N Noerachmanto MA, MSc, MAPS (Centers for Disease Control and Prevention, 2007)
IntroductionMotivational interviewing techniques have been minimally researched as a function of a teenage smoking intervention. The present study examined the efficacy of a theory-based motivational tobacco intervention (MTI).MethodsA randomized two-group design was used to compare 6-month post-baseline quit and reduction rates among teenagers who received the MTI with those who received brief advice or care as usual. Participants were smokers aged 14 to 19 years (N = 75) who presented for treatment in a university-affiliated hospital emergency department (ED). Motivational interviewing techniques were used by trained providers to facilitate individual change; stage-based take-home materials also were provided.ResultsSimilar to past clinic-based studies of motivational interviewing with teenage smokers, our study found negative results in terms of intervention efficacy for cessation. Six-month follow-up cessation rates were nonsignificant - two teenagers quit smoking. Among teenagers who were available at follow-up, a medium effect size (Cohen's h = .38) was found for reduction and a large effect size (Cohen's h = .69) was found for percentage reduction, although these results also were not statistically significant.ConclusionAlthough the major findings of this study were not significant, the reductions in tobacco use suggest that motivational interviewing may be a clinically relevant counseling model for use in teenage smoking interventions. However, many questions remain, and the current literature lacks studies on trials with significant outcomes using motivational interviewing in smoking cessation. Additionally, more research is needed to examine the suitability of the ED for MTI-type interventions.